The MAGNUM survey: a high-resolution study of the complex nuclear environment of local Seyfert galaxies - Mingozzi, M.; Venturi, G.; Mannucci, F.; Marconi, A.; Cresci, G.
The central regions of Seyfert galaxies, comprising broad and narrow line regions and the inner parts of galaxy disk and bulge, is characterized by a complex interplay among many physical effects. Specigically, it is shaped by the in uence of the central black hole, producing ionization by an hard continuum and gas out ows. The integral-field spectrograph MUSE at the ESO VLT allows to carry out a detailed study of these regions to obtain their ionization, dynamical, and metallicity properties. Here we present some highlights of the MAGNUM survey which is designed to study the central regions of a sample of nearby (D<50Mpc) Seyfert galaxies. We describe the rationale of the survey, the data analysis techniques used to extract information on ionization and dynamics, and the results for one galaxy, Centaurus A.
Keywords: Astronomy